2020
DOI: 10.1590/1983-40632020v5058854
|View full text |Cite
|
Sign up to set email alerts
|

Gas exchanges and growth of soybean cultivars submitted to water deficiency

Abstract: ABSTRACT A low availability of water in the soil may alter morphological traits and physiological processes in soybean, limiting its development, mainly at late sowings. This study aimed to evaluate the leaf gas exchanges and dry matter accumulation in soybean cultivars under low water availability at late sowing. An Oxisol with a very clayey texture was employed. A completely randomized design, in a 5 × 3 factorial scheme, with four replications, was used. The treatments were five water tensions (10 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Stomatal conductance (gs) in treatments under full irrigation (690.8 mmol H2O m -2 s -1 ) was higher than that of treatments under deficient irrigation (487.6 mmol H2O m -2 s -1 ) (Figure 3). Machado Junior et al (2017) and Silva et al (2020) also observed gs reductions in soybeans under soil water restriction. Stomatal conductance was the highest when solar radiation was high and leaf water potential had not yet reached minimum values to induce stomatal closure.…”
Section: Vegetation Indexes and Gas Exchangementioning
confidence: 88%
See 1 more Smart Citation
“…Stomatal conductance (gs) in treatments under full irrigation (690.8 mmol H2O m -2 s -1 ) was higher than that of treatments under deficient irrigation (487.6 mmol H2O m -2 s -1 ) (Figure 3). Machado Junior et al (2017) and Silva et al (2020) also observed gs reductions in soybeans under soil water restriction. Stomatal conductance was the highest when solar radiation was high and leaf water potential had not yet reached minimum values to induce stomatal closure.…”
Section: Vegetation Indexes and Gas Exchangementioning
confidence: 88%
“…Fine Sand Silt Clay Textural Classification ---------------------------g kg -1 ---------------------------- Fertilization was managed based on the soil chemical analysis. Nitrogen (urea), phosphorus (simple superphosphate), and potassium (potassium chloride) were applied to the soil, while micronutrients were sprayed on leaves (Silva, 2021). The dose of 1,000 kg N ha -1 was selected to meet soybean N demands throughout the crop season so that both cultivars could express their maximum yield potentials (6 Mg ha -1 expected yield).…”
Section: Sandmentioning
confidence: 99%
“…The accumulation of total dry mass is important for soybean productivity; however, it is affected by water stress. The decrease in plant biomass under severe stress is related to the effects on stomatal closure and decreased net photosynthesis (Silva et al, 2020). However, the nonsignificant difference in grain dry mass between WW and WS-R1+R5 demonstrates memory to minimize the effect of stress, maintaining the production of photoassimilates, partitioning them, and allocating them more efficiently, resulting in the maintenance of grain production.…”
Section: Proline Accumulation Is a Key Component Of Soybean Responses...mentioning
confidence: 99%
“…The internal CO 2 concentration (Ci; µmol CO 2 m −2 s −1 ), transpiration rate (E; mmol H 2 O m −2 s −1 ), stomatal conductance (gs; mmol H 2 O m −2 s −1 ), and net photosynthetic rate (A; µmol m −2 s −1 CO 2 ) were evaluated using a portable gas exchange device (LC-PRO+, ADC Bioscientific Ltd. Hoddesdon, UK) under a photosynthetically active radiation (PAR) of 1200 µmol m −2 s −1 . Based on these data, water use efficiency (WUE; µmol CO 2 mmol −1 H 2 O) was calculated through A/E [21].…”
Section: Characteristics Evaluatedmentioning
confidence: 99%